Effect of Feeding Bypass Fat on Reproductive Performance in Surti Buffaloes - Patel, Parimal D.; Patel, Dilipkumar C.; Parmar, Ajaykumar P.; Parmar, Abhishek B.; Sarvaiya, Nitesh P.; Joshi, Prakash M. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
An experiment was conducted to evaluate the effect of feeding bypass fat on reproductive performance of Surti buffaloes. Fourteen advanced pregnant Surti buffaloes were selected based on their records of daily milk yield and milk fat percent. The buffaloes were divided into two groups: Control (T1) and Treatment group (T2) with seven animals in each group. The buffaloes in control group were fed with green fodder, dry fodder and concentrate mixture as per ICAR requirements, while animals of treatment group received the same ration but were supplemented with bypass fat @ 130 g/d prepartum for one month and 30 g/kg milk yield for three months postpartum. The days required for uterine involution was significantly (p <0.05) reduced by 7 days (32.00 ± 0.76 vs. 39.29 ± 0.97) in bypass fat supplemented group as compared to control group. First estrus (50.29 ± 1.25 vs. 62.29 ± 0.57 days) observed after calving (days) and service period (81.14 ± 7.81 vs. 97.00 ± 10.44 days) were decreased (p <0.05) by 12 and 16 days, respectively, in bypass fat supplemented group over control. The number of service per conception was also reduced (1.43 ± 0.20 vs. 2.71 ± 0.18, p <0.05) with higher conception rate (85.71 vs 57.14 %) in bypass fat supplemented group as compared to control group. It was concluded that supplementation of bypass fat peripartum to Surti buffaloes hastens uterine involution and significantly improves postpartum fertility.